2017
DOI: 10.4143/crt.2016.054
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Chemotherapy for Advanced Gastric Cancer in Elderly and Non-elderly Patients: Meta-Analysis of Randomized Controlled Trials

Abstract: PurposeThis study evaluated the benefits of adjuvant chemotherapy on elderly patients with advanced gastric cancer (AGC) using meta-analysis of well-designed randomized controlled clinical studies.Materials and MethodsPubMed, Embase, and Cochrane were searched to retrieve clinical studies evaluating the benefits of adjuvant chemotherapy in the elderly with AGC. Hazards ratios (HRs) with 95% confidence intervals (CIs) were pooled across studies using a fixed-effects model.ResultsTwo studies were included in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…Our results also indicated that chemotherapy or radiotherapy had limited benefits in this elderly group, regardless if used in neoadjuvant or adjuvant setting if they received a curative surgical resection. This result was consistent with previous small cohort studies which demonstrated that elderly patients did not benefit from neoadjuvant or adjuvant treatment [45][46][47][48], especially for patients older than 80 years [49]. There are a limited number of studies that have reported a survival benefit for adjuvant chemoradiation therapy [50,51].…”
Section: Discussionsupporting
confidence: 91%
“…Our results also indicated that chemotherapy or radiotherapy had limited benefits in this elderly group, regardless if used in neoadjuvant or adjuvant setting if they received a curative surgical resection. This result was consistent with previous small cohort studies which demonstrated that elderly patients did not benefit from neoadjuvant or adjuvant treatment [45][46][47][48], especially for patients older than 80 years [49]. There are a limited number of studies that have reported a survival benefit for adjuvant chemoradiation therapy [50,51].…”
Section: Discussionsupporting
confidence: 91%
“…These results suggested that S-1 treatment was insufficient in eliminating micrometastatic cancer cells in cases with high p-TNM stage. Furthermore, in their subgroup analysis, S-1 treatment was shown to be not beneficial in elderly patients (≥ 60 years) and could not be sustained up to one year, with a 12-mo completion rate of only 65.8%[ 16 ]. In the CLASSIC study, only 67% received the planned eight cycles of adjuvant capecitabine and oxaliplatin chemotherapy; 56% experienced grade 3 or 4 adverse events; and 90% needed dose modifications because of adverse events[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent metaanalysis of adjuvant therapy for gastric cancer reported no benefit of adjuvant chemotherapy among the elderly population. 36 In contrast, in a separate study by Jo et al, the authors reported that adjuvant chemotherapy may confer a potential survival benefit in elderly patients with stages II or III gastric cancer after a D2 resection. 37 These data suggest that a different strategy and risk stratification may be needed for the elderly patients that considers their functional, social, and mental conditions.…”
Section: Discussionmentioning
confidence: 92%